Tax Revenue, FDI, and Agricultural Sector: A Dynamic Interaction with Regulatory Quality as the Moderation - Firda Maharani Anwar; Suparna Wijaya (Ilomata International Journal of Tax and Accounting, 2023)
This study aims to analyze the effect of Foreign Direct Investment (FDI), and share of agriculture on Tax Revenue in ASEAN countries with Regulatory Quality as the moderating variable. The research method used is descriptive quantitative with panel data regression analysis and the econometric model is estimated by Panel Corrected Standard Errors (PCSE). The result indicates that FDI, share of agriculture, regulatory-quality-moderated FDI and share of agriculture simultaneously have a significant effect on Tax Revenue. Partially, the result shows that FDI has a positive and significant effect on Tax Revenue. Regulatory Quality and Share of Agriculture have no effect on Tax Revenue. Furthermore, Regulatory Quality weakens the positive relationship of FDI and Tax Revenue, whereas Regulatory Quality strengthens the negative relationship between Share of Agriculture and Tax Revenue. Based on the generated results, there will be a necessity for government to create a comprehensive economic and fiscal policy to increase tax revenue and to strengthen the tax base in the ASEAN countries.